New Jersey Statewide Criminal Justice Guidelines Evaluation, 1979 - Sparks, Richard F. ([Verlag nicht ermittelbar], 1984)
This data collection is the result of a project established to study the development, implementation, and use of statewide sentencing guidelines and to report the perceptions of criminal justice system personnel and inmates regarding those guidelines. Funded by the National Institute of Law Enforcement and Criminal Justice, the project was carried out by the Rutgers University School of Criminal Justice from October 1978 to June 1981. Additional data produced by this project are contained in two other studies held by ICPSR: MASSACHUSETTS STATEWIDE STATEWIDE CRIMINAL JUSTICE GUIDELINES EVALUATION, 1979: SENTENCTING DATA (ICPSR 7909) and NEW JERSEY STATEWIDE CRIMINAL JUSTICE GUIDELINES EVALUATION, 1980: INMATE SURVEY DATA (ICPSR 7911). The data in this study is contained in two files. It consists of interviews to determine the opinions of inmates about the relative seriousness of offenses, severity of punishments, appropriateness of penalties for various kinds of crimes, and the use of sentencing guidelines to structure judicial sentencing decisions. Part 1, Inmate Background Data, contains socioeconomic, residential, and current and prior criminal history information in a random sample of 226 Rahway, New Jersey, State Prison inmates. Background information was collected for all of the inmates selected to participate in the 1979 New Jersey inmate survey. However, not all of those inmates selected agreed to be interviewed when the actual survey was conducted. Therefore, Part 1 includes information on survey respondents and nonrespondents. Part 2, Inmate Survey Data, contains information on 146 inmates. Frequency distributions and the survey instrument are included in the documentation.